Exercise Reduces H3K9me3 and Regulates Brain Derived Neurotrophic Factor and GABRA2 in an Age Dependent Manner - Ionescu-Tucker, Andra; Butler, Christopher W.; Berchtold, Nicole C.; Matheos, Dina P.; Wood, Marcelo A.; Cotman, Carl W. (Frontiers in Aging Neuroscience, 2021)
Exercise improves cognition in the aging brain and is a key regulator of neuronal plasticity genes such as BDNF. However, the mechanism by which exercise modifies gene expression continues to be explored. The repressive histone modification H3K9me3 has been shown to impair cognition, reduce synaptic density and decrease BDNF in aged but not young mice. Treatment with ETP69, a selective inhibitor of H3K9me3’s catalyzing enzyme (SUV39H1), restores synapses, BDNF and cognitive performance. GABA receptor expression, which modulates BDNF secretion, is also modulated by exercise and H3K9me3. In this study, we examined if exercise and ETP69 regulated neuronal plasticity genes by reducing H3K9me3 at their promoter regions. We further determined the effect of age on H3K9me3 promoter binding and neuronal plasticity gene expression. Exercise and ETP69 decreased H3K9me3 at BDNF promoter VI in aged mice, corresponding with an increase in BDNF VI expression with ETP69. Exercise increased GABRA2 in aged mice while increasing BDNF 1 in young mice, and both exercise and ETP69 reduced GABRA2 in young mice. Overall, H3K9me3 repression at BDNF and GABA receptor promoters decreased with age. Our findings suggest that exercise and SUV39H1 inhibition differentially modulate BDNF and GABRA2 expression in an age dependent manner.